"Surprise" in the evolution of chronic membranoproliferative glomerulonephritis associated with severe strongyloidiasis under corticotherapy: "hygienic paradox"?. (August 2013) - Gluhovschi, Gheorghe; Gluhovschi, Cristina; Velciov, Silvia; Ratiu, Iulia; Bozdog, Gheorghe; Taban, Sorina; Petrica, Ligia
Abstract A case of strongyloidiasis in a patient with membranoproliferative glomerulonephritis is reported. In our patient, strongyloidiasis evolved latently and became overt after corticotherapy, and it turned to be a very severe outcome and life-threatening complications, hyperinfection syndrome and upper digestive tract hemorrhage. Besides its well-known complications, steroid therapy may provide real surprises. The association of this therapy with strongyloidiasis may turn an undiagnosed inactive, chronic form of the disease into an active form within the framework of a hyperinfection syndrome which might lead to death. In our case, the diagnosis of strongyloidiasis was established only after duodenal biopsy was performed for upper digestive tract hemorrhage, which revealed the parasite. It should be underlined that under corticotherapy, the patient evolved favorably with regard to glomerular disease, while strongyloidiasis worsened. The outcome was positive after the patient was treated with albendazole and ivermectin. The diagnosis of strongyloidiasis is sometimes difficult to establish due to the fact that eosinophilia may be absent, while commonly utilized stool examinations may be negative. By analyzing our case, it may be assumed that the immune mechanisms involved in strongyloidiasis do not activate the glomerular nephropathy. On the contrary, these mechanisms seem to have an immunosuppressive effect. The "hygienic hypothesis" also needs to be considered. While on corticotherapy, patients with glomerulonephritis need immunologic and parasitologic monitoring. This is important for other immunodepressing diseases and for immunosuppressive drugs. If the patient has originated in a mining area, as is the case with our patient, or in endemic areas, this monitoring becomes mandatory. The case reflects the complexity of the interrelation between the immune mechanisms in glomerulonephritis and those in parasitic diseases, strongyloidiasis in our case.